Pengaruh Persepsi Harga, Citra Merek, dan Lokasi Terhadap Keputusan Pembelian di CFC Grande Karawaci - Clarita, Novia (AKSIOMA : Jurnal Manajemen, 2023)
In the restaurant industry, consumer purchase decision become the most important aspect in the life of the company because it can influence profitability, specifically for CFC Grande Karawaci. This study aims to analyze the impact of price perception (X1), brand image (X2), and location (X3) as an intervention variables on purchase decision (Y) at CFC Grande Karawaci. This research design uses a survey-based quantitative research design using a accidental sample method with (n=100) who had made purchase at CFC Grande Karawaci. The data were analyzed using multiple regression analysis. With primary data collected directly from respondents. According to research findings, purchase decision at CFC Grande Karawaci does not effect by brand image. As well as price perception and location had a significant effect at CFC Grande Karawaci. Finally, it can be concluded that price perception and location is the important aspect at CFC Grande Karawaci purchase decision.